Solidification and Stabilization (S/S) of Toxic Waste: Potential Binder for Partial Cement Replacement Materials (PCRM) - Ishak, E.A. (IOP Publishing Ltd, 2020)
Solidification and stabilization (S/S) in toxic waste treatment has been used widely in transform waste into sustainable construction materials. However, some parties is just using this treatment method in modify the toxic waste into a non-toxic form for its suitability in landfill. This action should not occur as proper waste management, should include both 'treat'; reduce toxicity (e.g: immobilize contaminants) and 'control'; reduce amount of waste generation (e.g: recycle). The perspective of 'dump is cheaper than recycle' has closed the eyes of the parties on the mesmerizing effect of S/S method in develop a sustainable construction masterials. Based on the past research, this happened due to the inability of the solidified waste to meet the construction materials requirements. Strength reduction and existence of toxic elements in leachate have been identified as the main factors that limit the application of solidified waste in construction industry. Nevertheless, the issue can be mitigate by using a proper binder to immobilize and encapsulate the toxic waste. Thus, this study aims to mitigate the issue by proposing a few binders that promotes high quality and sustainability to improve the S/S product. From the analysis, selection of binder relies on the chemical (e.g; high silica content) and physical (e.g; size) composition of the materials. Hence, pozzolanic materials have been chosen as usage of additional pozzolanic materials as partial cement replacement materials is promising in increase the strength of solidified waste and reduce its porosity. The pozzolanic materials mentioned in this study are industrial waste in approach to promote sustainability. Consequently, this study recommended the combination of pre-treatment such as thermal treatment, in reduce toxicity of toxic waste before S/S process to tackle the leachant or leachate issue and further adding pozzolanic materials for further strength development. Â© Published under licence by IOP Publishing Ltd.